Ellie Guthart: capstone - Guthart, Ellie, artist (Colorado State University. Libraries, 2026)
The artist's statement: I was unaware that coming to Colorado State University I would discover the medium of printmaking and spend most of my days in nitrile gloves handling hazardous materials. Some of my first printmaking courses such as Lithography and intaglio taught me a foundation in materiality, layering, and chemical reaction. I found myself rejecting the figurative approaches and traditional mark making. Instead, I became interested in how liquid materials move and form shapes of the human experience. Early on, I was drawn to the expressive capabilities of tusche wash in lithography, but it wasn't until later when I encountered the monotype process that I could expand within scale and energy. For years I had been using mineral spirits to clean up ink, admiring the reaction the solvent had on the thick colors. This led me to decide to put this reaction on a print itself, negating the inherent archival quality and tradition of replicability of printmaking. I consider my process, "mineral spirit mayhem" often laying flat fields of color intervening with mineral spirits or linseed oil. These works are formed from my lived experience, specifically my relationship to place. Growing up in Iowa, I often felt stunted by a space too small for the life I aspired to have. My move West inspires me to express themes of transition and freedom in my work. I use natural materials in the process and create motifs of flora, fauna, and figs to symbolize my connection with space and self.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: printmaking